Systematic review of health-related quality of life in patients undergoing pelvic exenteration. Issue 8 (August 2016) - Harji, D.P.; Griffiths, B.; Velikova, G.; Sagar, P.M.; Brown, J.
Abstract: Background: Pelvic exenteration is a radical operative treatment reserved for the management of a number of advanced primary and recurrent pelvic malignancies, including, rectal, gynaecological and urological. The advances in radiological staging, surgical techniques and greater use of chemotherapeutic agents haves translated clinically into improvements in the overall survival of this cohort of patients, irrespective of underlying disease pathology. Consequently, a greater proportion of the surviving population will present to healthcare professionals with a range of physical and psychological issues, therefore the profiling and understanding of the health-related quality of life (HrQoL) is integral to the long term management of this cohort of patients. The aim of this systematic review is to identify HrQoL themes from the current literature relevant to patients undergoing a pelvic exenteration. Methods: Literature searches were performed in three databases: MEDLINE (1975–November 2015), EMBASE and CINAHL. Each study was evaluated with regards to its design and statistical methodology. Data quality was reviewed in accordance with the Newcastle-Ottowa score and Critical Appraisal Skills Programme Checklist (CAPS) for quantitative and qualitative data accordingly. A narrative synthesis of all identified HrQoL issues was undertaken using the principles of content analysis. Results: A total of 24 studies were identified; 20 quantitative and 4 qualitative with 976 patients assessed in total. HrQoL was assessed as the main primary endpoint in 15 studies. The majority of studies were retrospective. Baseline data prior to the initiation of treatments were available in 6 studies alone. Nine themes were identified across the literature, which included body image, social impact, sexual function, treatment expectations, symptoms, communication, psychological impact, relationships and work and finance. Conclusions: Pelvic exenteration has a wide ranging impact on patients HrQoL affecting a range of physical and psychological domains.